Efficacy of bivalent fimbrial vaccines to control and eliminate intermediate forms of footrot in sheep. Issue 3 (12th December 2021) - Smith, KJ; Whittington, RJ; Corrigan, MA; Edmonstone, BI; Cronin, NA; Dhand, NK; Dhungyel, OP
Abstract : Objective: The aim of this study was to determine the efficacy of serogroup‐specific bivalent fimbrial vaccines in the control and elimination of relatively mild (intermediate) forms of footrot in sheep flocks in NSW, there being some evidence that such forms are difficult to control. Methods: Four flocks of sheep with history of footrot of intermediate virulence were selected based on clinical and bacteriological diagnoses. Dichelobacter nodosus serogroups included in bivalent vaccines at each farm were based on on‐farm serogroup‐prevalence data. Two doses of bivalent vaccine were administered with a 4‐week interval between doses. Repeated post‐vaccination inspections of all feet of between 100 and 119 animals per mob were conducted and foot swabs were collected for bacteriological testing. Blood samples were collected from 10 to 24 individually identified animals per flock at each inspection to check for agglutinating antibody responses. Results: In the majority of animals, antibody levels for serogroups included in each vaccine were above the level believed to be required for protective immunity. Footrot disappeared on farm 1 prior to vaccination, but did not reappear postvaccination. Footrot was controlled but not eliminated on farms 2, 3, and 4, where the prevalence and severity of the disease and number of serogroups present were reduced. Conclusion: Serogroup‐specific bivalent vaccines can be effective at controlling footrot caused by intermediate strains of D. nodosus .